2016
DOI: 10.18632/oncotarget.14251
|View full text |Cite
|
Sign up to set email alerts
|

Circulating thyroid stimulating hormone receptor messenger RNA and differentiated thyroid cancer: A diagnostic meta-analysis

Abstract: Thyroid stimulating hormone receptor messenger RNA (TSHR-mRNA) is over-expressed in thyroid cancer patients, which indicates that TSHR-mRNA is a potential biomarker of thyroid cancer. However, system evaluation for TSHR-mRNA as a diagnostic biomarker of thyroid cancer is deficient. The performance of TSHR-mRNA for thyroid cancer diagnosis was evaluated in this study. Three common international databases as well as a Chinese database were applied for literature researching. Quality assessment of the included li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The macro and SAS code used were included in the online, http://link.springer.com/article/10.3758/BRM.41.1.35 Statistical analyses were performed by Stata 12.0 (Stata Corporation, College Station, TX, USA) and P values of two-sided less than 0.05 were considered statistically significant. Heterogeneity among studies was assessed using I 2 statistics, which test total variation across studies [ 55 , 56 , 64 , 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…The macro and SAS code used were included in the online, http://link.springer.com/article/10.3758/BRM.41.1.35 Statistical analyses were performed by Stata 12.0 (Stata Corporation, College Station, TX, USA) and P values of two-sided less than 0.05 were considered statistically significant. Heterogeneity among studies was assessed using I 2 statistics, which test total variation across studies [ 55 , 56 , 64 , 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…They are mainly known for their role as ligand-dependent TFs, and the THRs bind to the thyroid hormone RE irrespective of the presence or absence of thyroid hormone to modulate the expression of target genes [ 374 ]. It was observed that the expression of THR was upregulated in thyroid cancer patients [ 375 ]. In addition, the levels of THR α 1 was also highly upregulated in human CRC patients and was found to modulate the Wnt pathway [ 128 ].…”
Section: Nuclear Receptors In Colorectal Cancermentioning
confidence: 99%
“…Until now, only a few circulating mRNA markers have been reported. For example, tyrosinase mRNA can be detected in the blood of some melanoma patients (10); telomerase mRNAs can be detected in breast cancer patients (11), CK19, mammaglobin, 5T4, and circulating thyroid-stimulating hormone receptor (TSHR) mRNAs can be detected in thyroid cancer patients (12); 5T4 mRNA can be detected in lung cancer patients (13); and CEA and CK19 mRNAs can be detected in colorectal cancer patients (14). These studies have revealed that circulating mRNAs can be potential biomarkers.…”
mentioning
confidence: 99%